GENETIC EVALUATION OF PHENAZINE SYNTHSIZED BY PSEUDOMONAS AERUGINOSA ISOLATED GENITAL TRACT OF FARM ANIMALS - & et al., Muhaidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The present study was carried out to isolate of Pseudomonas aeruginosa from the genital tract of some farm animals in Baghdad city to study the genetic and the ability of these isolates to produce phenazine pigment. For this purpose 240 vaginal and uterine samples were taken from 20 cows, 20 ewes and 20 goats postpartum. The result refer to that 203 samples gave positive bacterial growth. Distributed as follows 54 cows, 73 ewes and 76 goats. Depending on cultural, microscopic and biochemical characteristics, 17 isolates of P. aeruginosa were obtained. Addition to using differential and selective media to study the ability of these isolates to produce pyocyanin pigment. The results showed that all of P. aeruginosa were produced pyocyanin pigment in various amounts. Identification of phenazine was done using thin layer chromatography and high performance liquid chromatography. Results indicated that the compound separated from liquid culture was characterized as a phenazine. Genetic analysis for P. aeruginosa isolates was conducted to determine the location of genetic determinants for production of phenazine. Results showed that 8 isolates of P.aeruginosa had one plasmid band and 3 isolates had two, while 6 isolates had no bands which cured by using 275 μg /ml of ethidium bromide. The cured cells of isolates were examined for their ability of phenazine production. the cured cells continued to produce phenazine pigment. Amplification of chromosomal phz genes of isolates were done using PCR with specific primers. Bands of 1110 bp were characterized as related to the phz genes.